Nazywanie i poznawanie pewnej części krajobrazu – pojęcie łąka i jego wykładniki leksykalne w świetle dawnych oraz współczesnych słowników i źródeł encyklopedycznych - Bożętka, Barbara (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The work presented here focuses on the meaning of the word and term łąka (meadow) in the Polish language, with its examination based on contemporary and historical lexical and encyclopaedic sources. An analysis of this lexeme has been broadened by the study of related words, e.g.: pastwisko (pasture), łęg (demonstrating two meanings in Polish: a marshy meadow and a riparian forest), hala (a mountain glade in the sense of alpage), and polana (a glade). Contemporary definitions have been compared to those present in history, and represented in relevant historical sources. The comparison allowed the author to trace the changes in general meaning and in (overlapping) meaning areas. The research demonstrates that the word łąka has got a rather long history (the sources elaborated on by Słownik staropolski [Old-Polish dictionary] prove that the word first appeared in 1270), and it is still vivid and up-to-date. Evidence shows that the distinct features of the word łąka, represented in relevant lexicography, have been shaped by spatial, environmental and land-management connotations.